La importancia del comercio internacional del sector agropecuario en la economía ecuatoriana en la última década - Arias Galarza, Dayana Estefania (Machala : Universidad Técnica de Machala, 2022)
Té purpose of this work is to analyze the importance of International Trade in the agricultural production of Ecuador in the last decade. The relationships between the Gross Domestic Product (GDP) and the national agricultural Gross Domestic Product (GDP) are investigated, their variations during the period 2011 - 2020, and the exogenous changes in the aforementioned sector. Quantitative and descriptive information was collected from official statistical publications related to GDP, main destinations of agricultural productivity, rural population and agricultural employment. The main results revealed that the dynamics of the Ecuadorian international trade in the last decade have maintained a growth trend, the agricultural GDP has maintained a participation of 9.20% of the total GDP, and the main crops that make up the main income product of the exports are bananas, shrimp, cocoa, etc.
Este trabajo tiene por objeto analizar la importancia del Comercio Internacional en la producción agropecuaria del Ecuador en la última década. Se investigaron las relaciones entre el Producto Interno Bruto (PIB) y el Producto Interno Bruto agrícola (PIB) nacional, sus variaciones durante el periodo 2011 – 2020, y los cambios exógenos en el mencionado sector. Se recopiló información cuantitativa y descriptiva de las publicaciones estadísticas oficiales relacionadas con el PIB, principales destinos de la productividad agrícola, población rural y empleo agropecuario. Los principales resultados revelaron que la dinámica del comercio internacional ecuatoriano en la última década ha mantenido una tendencia de crecimiento, el PIB agrícola ha mantenido una participación del 9,20% del PIB total, y los principales cultivos que componen el principal ingreso producto de las exportaciones son el banano, camarón, cacao, etc.
Keywords: COMERCIO INTERNACIONAL; PIB TOTAL; PIB AGRÍCOLA